The study of masculinity crisis reflected in the main character in Anna Todd’s ‘After’ - Zahra Rafikasari (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
This study aimed to identify the masculinity crisis that reflected in the main character in Anna Todd’s ‘After’. The novel entitled ‘After’ is a famous from its web-released fanfiction web novel on Wattpad’s platform, then it published and filmed after. This study uses Connell theory on masculinity (Connell, 2005) to find the related data with the theory itself. Furthermore, this analysis focuses on the used theory of masculinity by detailing in masculinity crisis inside Hardin’s inferiority in the novel After by Anna Todd. In addition, the previous studies connected with the effect of failing two stages in Psychosocial Development on Hardin's personality by (Afifah, 2021).